INTEGRATING TECHNOLOGY IN ENGLISH CLASSROOM AT ELEMENTARY SCHOOL: EFL PRE-SERVICE TEACHER PERSPECTIVE - Diyan Adyanti; Yuliyanah Sain; Faridawati Faridawati; Rahmat Nasrullah (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
Effective technology integration is believed to be able to increase student motivation in learning while also helping teachers' work become easier. This research aims to determine pre-service teachers' perspectives on how technology is used to increase student motivation in learning English in elementary school students. This research focuses on learning applications used by pre-service teachers. Qualitative descriptive methods were used as the design of this research. Data were collected through semi-structured interviews involving two EFL students participating in a campus teaching program. The findings show that pre-service teachers use the Duolingo and Quizizz applications in teaching English. Integrating technology in the form of learning applications gets positive results where students are motivated to learn English because students seem more active and comfortable learning with the learning while playing system. So the use of technology is felt to be very fun and makes learning not become saturated and boring